Buying freedom : the ethics and economics of slave redemption - Appiah, Anthony; Bunzl, Martin (Princeton University Press, 2007)
"If "slavery" is defined broadly to include bonded child labor and forced prostitution, there are upward of 25 million slaves in the world today. Individuals and groups are freeing some slaves by buying them from their enslavers. But slave redemption is as controversial today as it was in pre-Civil War America. In Buying Freedom, Kwame Anthony Appiah and Martin Bunzl bring together economists, anthropologists, historians, and philosophers for the first comprehensive examination of the practical and ethical implications of slave redemption. While recognizing the obvious virtue of the desire to buy the freedom of slaves, the contributors ask difficult and troubling questions: Does redeeming slaves actually increase the demand for--and so the number of--slaves? And what about cases where it is far from clear that redemption will improve the material condition, or increase the real freedom, of a slave?"--Publisher description